The scientific revolution : how science and technology shaped the world - Kennon, Caroline (World history (Lucent Press), 2019)
Describes the birth of the Scientific Revolution, and explores its key ideas and discoveries, notable scientists and their achievements, and impact on the world. Includes a timeline, photographs, primary sources, and further resources.